ACOUSTIC EMISSION AT CHANGE OF CONTACT INTERACTION AREA OF FRICTION UNIT OF COMPOSITE MATERIAL - Filonenko, Sergiy; Kosmach, Oleksandr; Kositskaya, Tetyana (Proceedings of National Aviation University (archive), 2014)
The results of simulation of resulting acoustic emission signals at friction surfaces of the composite material were shown. It was shown that at increase of contact interaction area of the friction unit is increase of the average amplitude of the acoustic emission, their standard deviation and variance. The approximation expressions for the regularities of changes of the amplitude parameters of acoustic emission signals which are generated by the increase of the contact interaction area of the friction unit were defined. The comparison of experimental results with theoretical research was conducted. It was shown that the most sensitive parameter to change the contact interaction area of the friction unit is the variance of the average amplitude of the formed resultant acoustic emission signal